Carbon fibre surface modification using functionalized nanoclay: A hierarchical interphase for fibre-reinforced polymer composites. (18th August 2017) - Zabihi, Omid; Ahmadi, Mojtaba; Li, Quanxiang; Shafei, Sajjad; Huson, Mickey G.; Naebe, Minoo
Abstract: Low interface strength is a common challenge in taking full advantage of excellent physical performances of carbon fibre (CF) reinforced polymer composites. Herein, for the first time, we have used amino-functionalized nanoclay as a linkage between CF surface and epoxy matrix, which by a cation exchange process was grafted on the CF surface. Amino-functionalized nanoclay significantly increased surface roughness, coefficient of friction, and BET surface area of CF. The results showed that nanoclay-based modification does not change the tensile strength and Weibull modulus of CF significantly however, both specific and dispersive surface energies, obtained by inverse gas chromatography technique, were increased. A high compatibility of nanoclay-based modified CF (clay@CF) with epoxy resin was also observed by analysing the contact angle between epoxy droplets and fibre surface. Moreover, single fibre fragmentation tests (SFFT) alongside fractographic observations showed that the length of fibre pull-out and the size of cracks between the fibre and matrix were outstandingly reduced in clay@CF in comparison to untreated CF, demonstrating that the stress transfer and interfacial shear strength (IFSS) have been significantly improved.